2016
DOI: 10.4168/aair.2016.8.6.522
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Matrix Metalloproteinase-9 in Children With Chronic Spontaneous Urticaria

Abstract: PurposeChronic spontaneous urticaria (CSU) is a disease that is primarily seen in adults and is comparatively rare in children. Consequently, only a few studies have focused on the pathogenesis of the disease in children. This study investigated the possible role of metalloproteinase-9 (MMP-9) in the pathogenesis of CSU in children.MethodsThe study group was composed of 54 children with CSU; 34 healthy children comprised the control group. The demographic and clinical features of the study group were extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Furthermore, MMP-9, produced by several inflammatory cells, including macrophages, neutrophils, T cells, and mast cells, promotes migration and activation of immune cells by cleaving pro-inflammatory chemokines and cytokines and therefore contributing to the inflammatory processes 68,69. However, some but not all studies showed an association between plasma levels of MMP-9 and disease activity 23,67,70. Therefore, further studies are required before considering MMP-9 as biomarker in the activity and progression of CSU 26.…”
Section: Biomarkers Of Angiogenesis Coagulation and Vascular Dysregumentioning
confidence: 99%
“…Furthermore, MMP-9, produced by several inflammatory cells, including macrophages, neutrophils, T cells, and mast cells, promotes migration and activation of immune cells by cleaving pro-inflammatory chemokines and cytokines and therefore contributing to the inflammatory processes 68,69. However, some but not all studies showed an association between plasma levels of MMP-9 and disease activity 23,67,70. Therefore, further studies are required before considering MMP-9 as biomarker in the activity and progression of CSU 26.…”
Section: Biomarkers Of Angiogenesis Coagulation and Vascular Dysregumentioning
confidence: 99%
“…Although elevated levels by themselves cannot explain the entire disease pathogenesis, the increased production of some cytokines, chemokines, or metabolites-including IL-6, vascular endothelial growth factor (VEGF), matrix metallopeptidase 9 (MMP-9), and reactive oxygen species-was reported in previous clinical studies. [46][47][48][49] LXs can inhibit the generation of pro-inflammatory cytokines and chemokines via the inhibition of transcription factors, such as NF-κB and activator protein 1. [50][51][52] In this regard, several in vitro studies and animal models have proven that LXA 4 and its analogues can decrease IL-6 secretion, 6 MMP-9 expression, 53 and VEGF expression 54 and can block ROS generation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Vascular Endothelial Growth Factor (VEGF) and the Calcitonin Gene-Related Peptide (CGRP) have been observed in the lesions of the patients with the highest levels of vasodilatory factors [58,59]. Of interest, VEGF is also an important vasodilator mediator, through the production of nitric oxide (NO).…”
Section: The Pathophysiology Of Urticariamentioning
confidence: 99%